Pergeseran Makna Ritual Rabu Abeh di Aceh: Ditinjau dari Konstruksi Sosial Peter L Berger - Wika Fitriana Purwaningtyas; Baehaki (Wahana Islamika Jurnal Studi Keislaman, 2026)
Rabu Abeh is an Acehnese cultural tradition that has historically undergone continuous transformation, beginning with ancestral beliefs, later intersecting with Islamic teachings, and eventually encountering modern societal influences. This study examines the Rabu Abeh ritual as practiced by communities in Aceh Province, where it functions as a tolak bala ritual intended to protect society from misfortune and disaster. The ritual is performed annually according to the Islamic calendar, specifically on the last Wednesday of the month of Safar. Its traditional forms include the offering of symbolic offerings and the recitation of verses from the Holy Qur’an; however, in recent developments, the ritual has gradually shifted into a social and recreational occasion shared with family members. This study employs a qualitative research method with library research as its primary data source and is framed within a sociological approach using Peter L. Berger’s theory of the social construction of reality. The findings reveal the stages of the ritual process and its relationship to social construction. Referring to Berger’s perspective, society is a human product, and humans are, in turn, products of society. This reciprocal relationship operates through three dialectical processes within social construction: externalization, objectivation, and internalization.